Twist1 contributes to cranial bone initiation and dermal condensation by maintaining wnt signaling responsiveness. Issue 2 (17th December 2015) - Goodnough, L. Henry; Dinuoscio, Gregg J.; Atit, Radhika P.
Abstract : Background: Specification of cranial bone and dermal fibroblast progenitors in the supraorbital arch mesenchyme is Wnt/β‐catenin signaling‐dependent. The mechanism underlying how these cells interpret instructive signaling cues and differentiate into these two lineages is unclear. Twist1 is a target of the Wnt/β‐catenin signaling pathway and is expressed in cranial bone and dermal lineages.Results: Here, we show that onset of Twist1 expression in the mouse cranial mesenchyme is dependent on ectodermal Wnts and mesenchymal β‐catenin activity. Conditional deletion of Twist1 in the supraorbital arch mesenchyme leads to cranial bone agenesis and hypoplastic dermis, as well as craniofacial malformation of eyes and palate. Twist1 is preferentially required for cranial bone lineage commitment by maintaining Wnt responsiveness. In the conditional absence of Twist1, the cranial dermis fails to condense and expand apically leading to extensive cranial dermal hypoplasia with few and undifferentiated hair follicles.Conclusions: Thus, Twist1, a target of canonical Wnt/β‐catenin signaling, also functions to maintain Wnt responsiveness and is a key effector for cranial bone fate selection and dermal condensation. Developmental Dynamics 245:144–156, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Changes in keratin expression seen during healing of wounds made near the limbus mimic changes seen during post-natal development. K14, a corneal epithelial stem cell enriched keratin, is localized within K8+ compound niches. K14 increases after wounding and remains elevated at times when K8+ compound niches expand in number. Data support the conclusion that limbal stem cells expand in number when the cornea is wounded near where limbal stem cells reside.